SELF-ACCEPTANCE AND LIFE SATISFACTION AMONG BREAST CANCER PATIENTS OF ISLAMABAD - Najam ul Hasan Abbasi; Seema Gul; Maryam Khurshid et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT:INTRODUCTION: It is acknowledged all over the world that breast cancer can aﬀect a woman's feelings of self-acceptance and life satisfaction, there are few studies concerning the level of selfacceptance and life satisfaction separately among women with breast cancer in Pakistan population. OBJECTIVES: To study the role of self-acceptance on life satisfaction among women with breast cancer, and to analyze the inﬂuence of socio-personal characteristics of women with their life satisfaction. DATA SOURCE & SETTINGS: A sample of 50 women (n=50) was selected from diﬀerent hospitals of Islamabad. PERIOD: The duration of the study was 6 months. METHODS: The present study made use of the two scales i-e., Satisfaction with Life Scale and SelfAcceptance Questionnaires. The random sampling technique was used to collect data of clinical group from diﬀerent hospitals of the Islamabad. RESULTS: Psychometric properties; alpha correlation, student t-test was used to analyze the data p value less than 0.05 was considered statistically signiﬁcant. The results showed that there was a signiﬁcant relationship between Self-acceptance and life satisfaction. The study also found that the low sense of identity as a whole, leads women to be dissatisﬁed with their lives. There was also a signiﬁcant diﬀerence in demographic variables on life satisfaction and self-acceptance. CONCLUSIONS: The level of self-acceptance among women with breast cancer in Islamabad was low. Several factors were found to be signiﬁcantly associated with the self-acceptance and life satisfaction of women with breast cancer.